The influence of green brand positioning, green brand knowledge, and environmental concern on green product purchase intention: A study of eco-friendly products by Nestlé Indonesia - Fitria, Nanda; Fihartini, Yuniarti (Lighthouse Publishing, 2025)
Environmental pollution in Indonesia is a problem that has not been effectively resolved. Recently, environmental health issues have become a serious concern. Based on a report from the world air quality agency IQAir in 2021, Indonesia was ranked 17th as the country with the highest level of air pollution in the world with a PM2.5 concentration reaching 34.3 μg (micrograms) per cubic meter. Responding to the issues circulating regarding environmental pollution, many companies have agreed to environmental protection as part of their responsibility and have begun to position their brands as brands that care about the environment. PT Nestle Indonesia is one of the food and beverage companies that has begun to strengthen its position as a company that cares about the environment by separating the company's growth from its total environmental footprint (waste/residue). The purpose of this study was to determine the effect of green brand positioning, green brand Knowledge, and environmental Concern on green product purchase intention among consumers of PT Nestle Indonesia. This study is a quantitative study with a sampling method using a research questionnaire filled out by 160 respondents domiciled in Bandar Lampung who have the intention to purchase environmentally friendly products from PT Nestle Indonesia. Data analysis conducted in this study used multiple linear regression through the SPSS 26 application. Empirical findings revealed that green brand positioning, green brand knowledge, and environmental concern have a positive and significant effect on the intention to purchase environmentally friendly products.